Parents' personality and their expectations about child's development - Begum, Taslima; Huque, Akibul-Ul- (© 2016 Universal Journal of Psychology., 2019)
This article was published in the Universal Journal of Psychology [© 2016] and the definite version is available at : http://doi.org/10.13189/ujp.2016.040502. The Journal's website is at: http://www.hrpub.org/journals/article_info.php?aid=4083